Lời giải
Đáp án đúng là: B
\(A:\frac{{x + 1}}{{{x^2} + x + 1}} = \frac{{{x^3} - 1}}{{{x^2} - 1}}\)
\(A = \frac{{{x^3} - 1}}{{{x^2} - 1}} \cdot \frac{{x + 1}}{{{x^2} + x + 1}} = \frac{{\left( {x - 1} \right)\left( {{x^2} + x + 1} \right)}}{{\left( {x - 1} \right)\left( {x + 1} \right)}} \cdot \frac{{x + 1}}{{{x^2} + x + 1}} = 1\)
Tìm giá trị của x để phân thức A chia hết cho phân thức B biết:
\(A = \frac{{{x^3} - {x^2} - x + 11}}{{x - 2}};\,\,B = \frac{{x + 2}}{{x - 2}}\).
Cho\(A = \frac{{{x^2} + {y^2} + xy}}{{{x^2} - {y^2}}}:\frac{{{x^3} - {y^3}}}{{{x^2} + {y^2} - 2xy}}\)và \(B = \frac{{{x^2} - {y^2}}}{{{x^2} + {y^2}}}:\frac{{{x^2} - 2xy + {y^2}}}{{{x^4} - {y^4}}}\).
Khi x + y = 5 hãy so sánh A và B.